2020
DOI: 10.1161/hypertensionaha.120.14971
|View full text |Cite
|
Sign up to set email alerts
|

Early and Supernormal Vascular Aging

Abstract: Pulse wave velocity is an established marker of early vascular aging but may also help identifying individuals with supernormal vascular aging. We tested the hypothesis that individuals with the largest difference (Δ-age) between chronological and vascular age show the lowest rate of cardiovascular events and may thus be defined as supernormal vascular aging. Vascular age was defined as the predicted age in the best fitting multivariable regression model including classical risk factors and treatment and pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 38 publications
0
69
0
1
Order By: Relevance
“…Similarly to the interaction of PSEN1 with the APOE ɛ3 Christchurch mutation, the effect of APOE ε4/ε4 homozygosity may be modulated by both non-APOE genetic variants associated with AD and environmental exposures (see below). A similar phenomenon is known in the field of vascular diseases, in which individuals featuring supernormal vascular ageing (SUPERNOVA) have been described who do not show age-dependent increased arterial stiffness in spite of a heavy cardiovascular risk factor burden 135,136 . Epigenetic mechanisms have been invoked to explain the SUPERNOVA phenomenon.…”
Section: [H2] Apoe ɛ4-related Sporadic Admentioning
confidence: 61%
“…Similarly to the interaction of PSEN1 with the APOE ɛ3 Christchurch mutation, the effect of APOE ε4/ε4 homozygosity may be modulated by both non-APOE genetic variants associated with AD and environmental exposures (see below). A similar phenomenon is known in the field of vascular diseases, in which individuals featuring supernormal vascular ageing (SUPERNOVA) have been described who do not show age-dependent increased arterial stiffness in spite of a heavy cardiovascular risk factor burden 135,136 . Epigenetic mechanisms have been invoked to explain the SUPERNOVA phenomenon.…”
Section: [H2] Apoe ɛ4-related Sporadic Admentioning
confidence: 61%
“…Early vascular aging (EVA) and supernormal vascular aging are two extreme vascular ageing phenotypes. EVA or arterial stiffness is a concept mentioned in the literature for the first time in 2008 [ 148 ] and includes premature changes in the structure and function of the arteries due to the action of cardiovascular risk factors, environmental factors, genetic predisposition or fetal programming [ 149 , 150 ]. On the other hand, supernormal vascular aging is defined as abnormally low arterial stiffness [ 151 ].…”
Section: Early Vascular Aging (Eva) Vs Supernormal Vascular Aging (Su...mentioning
confidence: 99%
“…Between these two entities, EVA and SUPERNOVA are patients with healthy vascular aging interpreted as low blood pressure and pulse wave velocity over 50 years old [ 155 ]. Bruno et al [ 148 ] demonstrated that estimation of the age difference between the vascular and chronological one might be a useful clinical tool for identifying patients with SUPERNOVA phenotype. Individuals with a vascular age at least 6 years younger than their chronological age are associated with a 40% lower risk of cardiovascular events compared to subjects with a normal vascular age despite the prevalence of cardiovascular risk factors.…”
Section: Early Vascular Aging (Eva) Vs Supernormal Vascular Aging (Su...mentioning
confidence: 99%
“…), amelyek szervezetünk érrendszerében -a micro-és a macrovascularis struktúrában egyaránt -végbemennek, hozzák létre a szöveti károsodásokat, majd a betegségeket [32]. Hypertoniában, illetve általában a systolés vérnyomás tekintetében a korral együtt járó növekedés rendszerint párhuzamos az atherosclerosis okozta folyamattal, illetve az ezt mérő artériás merevség (stiffness) folyamatos növekedésével [33]. Mindez megbízhatóan mérhető a CAC-pontrendszer alapján is [34].…”
Section: Mit Nyújtanak Számunkra Ezen Elemzések?unclassified